Hadith #200 - Sunan al-Nasa'i - Abd al-Jabbar bin al-'Ala' عبد الجبار بن العلاء بن عبد الجبار; Abdur Rahman bin al-Sa'ib al-Hilali عبد الرحمن بن السائب الهلالي; Abu Ayyub al-Ansari; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan al-Nasa'i)
“Water is for Water.” That is, water for peforming Ghusl is obligatory when the ejaculation of water (semen) occurs.
Grade:

Hadith #1398 - Sunan Ibn Majah - Abdullah bin 'Ubaidullah b. Abi Mulayka عبد الله بن عبيد الله بن أبي مليكة; Abdur Rahman bin al-Sa'ib al-Hilali عبد الرحمن بن السائب الهلالي; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي (Sunan Ibn Majah)
‘It is not an act of righteousness to fast while traveling.”
Grade: